(untitled) (European Journal of Marketing and Economics, 2020)
One of the four exhaustively formulated legal means for the emergence of a European company, Council Regulation (EC) No 2157/2001 of 8 October 2001 on the Statute for a European company (Societies Europaea –SE) is the constitution of a Subsidiary European company. Compared to the other legal models for establishing this new organizational form for business association in the company typology within the European Union, the establishment of this particular entity possesses its own specific characteristics. The regulatory framework for the establishment of a Subsidiary European company is of a hybrid legal type. On the one hand, it takes account of the Community Act Regulation. However, in a number of cases the Community Act refers to the national law of the Member State where the company has its registered office under its constitution within the Union, and where its head office is located. The article discusses the legal prerequisites and the individual components of the procedure for the establishment of a Subsidiary European company.